Cyclical drivers of euro area consumption: What can we learn from durable goods? - André Casalis; Georgi Krustev (European Central Bank (ECB), 2020)
We study the cyclical dynamics of consumption in the euro area (EA) and the large EA countries by distinguishing durable from nondurable expenditures. We adopt a theoretical partial equilibrium framework to justify the identification strategy of our empirical model, a time-varying parameter structural vector autoregression (TVP-SVAR). Following the main insight from the theoretical model, that liquidity constraints induce important interactions between durables and nondurables, we distinguish durable-specific demand and supply shocks, while taking into account monetary and credit conditions. Our main findings are: (i) durables react faster and more strongly than nondurables after monetary shocks in the euro area and in the largest EA countries, a confirmation of an outcome commonly reported for the US; (ii) there is a large degree of cross-country heterogeneity in how different factors (including durable-specific ones) explain consumption; (iii) the strength of spillovers from durable to nondurable consumption, as predicted by theory, is empirically correlated with how much households across countries are likely to be liquidity constrained.
Keywords: C11; C32; D11; E21; E32; 330; consumption; durable goods; SVARs; sign restrictions